2015
DOI: 10.1007/s00264-015-2856-x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical versus conservative treatment of primary patellar dislocation. A systematic review and meta-analysis

Abstract: Based on the available data, surgical treatment of primary patella dislocation significantly reduces the risk of patella redislocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 41 publications
1
32
1
4
Order By: Relevance
“…With regard to the question of clinical relevance, the results of this study support the idea of other authors of normalizing TT-TG to individual patient size, as we observed several significant correlations between TT-TG and parameters of joint size and leg length in patients with PFI. It has been reported that surgical treatment significantly reduces the risk of patellar redislocation [14]. An increased tibial TT-TG can be surgically addressed by medial transfer of the tibial tuberosity, and using an index instead of the absolute TT-TG value can be helpful when indicating operative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the question of clinical relevance, the results of this study support the idea of other authors of normalizing TT-TG to individual patient size, as we observed several significant correlations between TT-TG and parameters of joint size and leg length in patients with PFI. It has been reported that surgical treatment significantly reduces the risk of patellar redislocation [14]. An increased tibial TT-TG can be surgically addressed by medial transfer of the tibial tuberosity, and using an index instead of the absolute TT-TG value can be helpful when indicating operative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the recurrence rate of dislocation in the non-surgical group increased significantly after data aggregation. Moreover, predisposing factors for APPD were not equally distributed in the two treatment arms in most of the studies [18]. The anatomic factors that can predispose a patient to recurrent patellar instability include patella alta, genu valgum, torsional deformity, lateral patellar tilt, trochlear dysplasia, increased Q-angle, and elevated tibial tubercle-trochlear groove (TT-TG) distance [8].…”
Section: Efficacy Evaluationmentioning
confidence: 99%
“…Clinical randomized controlled trials (RCTs) have been conducted to compare surgery versus conservative treatment for APPD; the treatment that can best improve the clinical outcome is still debatable. Although, metaanalyses of related RCTs have been conducted [15][16][17][18], the latest one was published 3 years ago [19]. To offer the best evidence-based evidence available to the clinic, we performed the latest meta-analysis of randomized controlled trials (RCTs) that compare clinical results between surgery and conservative therapy of acute primary patellar dislocation (APPD), focusing on medial patellofemoral ligament (MPFL) reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Cryotherapy is useful in the first 48 hours of injury, but it can be used also in the following 3-4 weeks to address the joint effusion and the pain after exercise therapy and loading. Electrostimulation can prevent muscle atrophy, promote muscle strengthening, and facilitate functionally useful movements [82][83][84][85][86][87][88][89][90] .…”
Section: Physical Modalitiesmentioning
confidence: 99%